Risk–Benefit Assessment of Monomethylmercury and Omega-3 Fatty Acid Intake for Ringed Seal Consumption with Particular Emphasis on Vulnerable Populations in the Western Canadian Arctic - Gmelch, Lena; Hintelmann, Holger; Hickie, Brendan; Kienberger, Hermine; Stern, Gary; Rychlik, Michael (Frontiers in Nutrition, 2017)
Many northern Inuit communities rely on traditional food as major source of nourishment. An essential part of the traditional Arctic diet are marine mammals such as ringed seals or beluga. Being top predators these animals are often highly contaminated with various toxins. On the other hand, some tissues of marine mammals are also characterized by high amounts of n3-PUFAs (omega-3 polyunsaturated fatty acids). Here, we try to balance the risks associated with the consumption of different tissue types of ringed seals in terms of the neurotoxin MMHg (monomethylmercury) with the benefits of consumption due to high n3-PUFA concentrations. Fetuses are at the highest risk of neurological impairments since MMHg can easily cross the placental barrier. Therefore, women of childbearing age served as an indicator population for especially susceptible subpopulations. We calculated maximal weekly maternal portions sizes if mutual consumption of muscle and blubber tissue or liver and blubber tissue was assumed. Those weekly portion sizes resulted in an estimated overall IQ point gain of infants of 0, whereas the consumption of liver or muscle tissue without blubber could lead to an IQ loss. In contrast to former studies, our data do not generally prohibit the consumption of liver tissue. Instead, our results suggest that a maximal weekly consumption of 125 g liver tissue together with 1 g of blubber tissue is acceptable and does not lead to neurological damages in the long term. Similarly, the consumption of maximal 172 g muscle tissue can be balanced by the mutual consumption of 1 g blubber tissue.